Jelajah Digital Aman Jaya (JEDI) & Business Innovation Competition and Exhibition 2018 (BICE) / Khiriah Ibrahim - Ibrahim, Khiriah (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2018)
On May 14, 2018 Business Innovation Competition and Exhibition (BICE) had been organized by Department of Busi-ness Management, UiTM Perak Branch, Tapah Campus. Conducted twice a year, this programme has taken a step further by collaborating with KPerak. KPerak INC Corporation (KPerak) is a corporation set up by the State Government of Perak to oversee the development of ICT related activities in the state and is dedicated to assist businesses and link up various communities through the promotion of ICT. The organization also aims to assist Perak's vision of becoming the preferred ICT investment destination through multimedia innovations and operations.